2024
DOI: 10.1186/s12888-023-05486-1
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of psychological distress in the association between temperaments and dark future among young adults

Emmanuelle Awad,
Diana Malaeb,
Feten Fekih-Romdhane
et al.

Abstract: Objective The aim of the current study is to evaluate the moderating effect of psychological distress variables, depression, anxiety and stress on the relationship between affective temperaments and future anxiety, assessed with the Dark Future scale. Methods Lebanese adults from all districts/governorates of Lebanon participated in this cross-sectional study. The data was collected through a questionnaire including: a section about sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
4
4
0
Order By: Relevance
“…Concerning mental health outcomes, our results are in line with the literature on gender studies, which highlights the greater tendency toward the internalization of problems in women who, for this reason, are more exposed to psychological distress [94]. Our results also reiterate those that emerged in more recent studies on the greater increase in internalizing disorders in young adult women compared to young adult men [95] and those carried out during the pandemic, in which women were found to be more affected by internalizing symptoms, worries, and future anxiety [3,84]. Regarding Fear of War, our results reiterate those found in our previous study [50] and in other recent contributions [48,49], reporting greater levels of both conventional and nuclear Fear of War in women [43,45].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning mental health outcomes, our results are in line with the literature on gender studies, which highlights the greater tendency toward the internalization of problems in women who, for this reason, are more exposed to psychological distress [94]. Our results also reiterate those that emerged in more recent studies on the greater increase in internalizing disorders in young adult women compared to young adult men [95] and those carried out during the pandemic, in which women were found to be more affected by internalizing symptoms, worries, and future anxiety [3,84]. Regarding Fear of War, our results reiterate those found in our previous study [50] and in other recent contributions [48,49], reporting greater levels of both conventional and nuclear Fear of War in women [43,45].…”
Section: Discussionsupporting
confidence: 91%
“…Given that the relationship between Future Anxiety and Fear of War does not seem to have yet been investigated in contexts that are not directly involved in a war, at present it is impossible to compare these results with those of similar studies. Nevertheless, they are supported by other studies conducted on young adults, which highlight that anxiety about the future and the negative representation of the latter constitute risk factors for general malaise and in particular for Stress, Anxiety, and Depression [84,85]. On the contrary, the literature highlights that the ability to maintain a positive representation of the future in the face of sources of uncertainty and various stressors plays a protective function for the definition of identity, planning, and hope, and for a better general mental well-being [65,86].…”
Section: Discussionsupporting
confidence: 63%
“…Recently, in a study by Mutia and Hargiana [ 45 ], Future Anxiety appears to apply specifically to young adulthood, and contextual factors have a greater role in facilitating or hindering the growth process. In contrast, however, Awad et al [ 46 ] highlighted how significantly lower levels of Future Anxiety were found with advancing age, further highlighting the construct’s centrality in young adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The attitude of human beings toward the future varies greatly, ranging from optimism to pessimism. Therefore, several studies [ 4 , 5 ] explored how personality traits can affect the ability to deal with threats and decide if forthcoming events will be faced with worry, fear and stress. Moreover, the environment and current situation of a person (economic status, a disabled family member…) have been shown to affect their perception of the future; for instance, in Iran, a recent study [ 6 ] conducted among mothers with disabled children concluded that they experience higher levels of anxiety about the future, health, and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we excepted that this model would have invariance across women and men, which would be consistent with previous work [ 4 ], and have adequate concurrent validity with psychological distress and temperaments. For instance, a previous study [ 5 ] conducted in Lebanon suggested that experiencing psychological distress is a moderator for the relationship between negative temperament (anxiety and fear) and dark future.…”
Section: Introductionmentioning
confidence: 99%